Counseling on compliance with antenatal care visits for preventing delivery complications at bira health center 2024 - Jusmawati, Jusmawati; Hasrida, Hasrida (Journal of Evidence-Based Community Health, 2025)
Childbirth complications are the leading cause of maternal death. Data from the Ministry of Health's maternal death registration system, Maternal Perinatal Death Notification (MPDN), shows that the number of maternal deaths was 4,005 in 2022 and increased to 4,129 in 2023. Mothers often experience complications in childbirth, including cephalopelvic disproportion, amniotic fluid embolism, umbilical cord entanglement, fetal stress, bleeding, perinatal asphyxia, placental retention, and uterine atony. This is certainly a problem that requires the involvement of midwives as service providers to mothers and the community; for example, they must be trained in compliance with antenatal visits to reduce the risk of childbirth complications. This community service activity was carried out at the Bira Makassar Health Center on December 15, 2024. The main target of this activity was 12 mothers who made ANC visits. The purpose of this community service is so that mothers are more compliant in making ANC visits to prevent complications during the labor process, counseling participants can increase their knowledge and understand the counseling material that has been provided at the Bira Kapasa Health Center. Antenatal care is medical care provided to pregnant women before and during pregnancy with the aim of finding health problems of the mother and fetus, providing information about their health, and helping them prepare for childbirth. To reduce MMR and IMR, the government has made a policy to ensure that every mother has access to good and integrated antenatal health services. These services include 10 T (weighing, measuring height, blood pressure, checking the nutritional status of the uterine fundus, knowing the fetal heart rate and fetal presentation, providing tetanus vaccination, iron tablets, and laboratory tests for pregnant women). To reduce the risk of complications in childbirth, regular ANC visits are very important.